PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DHARMA BANDAR MANDALA YOGYAKARTA. - Maiki Rahmad (JURNAL EKOBIS DEWANTARA, 2018)
Dharma Bandar Mandala (DBM) is a Freight Forwarding company that provides air, sea and land transportation management services, in the management it is seen that the number of consumers is decreasing. This is allegedly due to the decline in employee performance, which is suspected due to the influence of various factors such as Leadership, Motivation and Work Environment. To analyze this problem used Regression analysis method by using 32 Respondents, its purpose is to analyze the influence of Leadership, Work Motivation and Work Environment partially and together to the performance and to find the most dominant influence among independent variables. The data obtained were analyzed by multiple linear regression technique at a significant level of 0.05. The results showed that: There is a significant influence between Leadership, Work Motivation and Work Environment on Performance, with the level of significance of the three variables 0.000.